Subclinical atrial fibrillation in patients with recent transient ischemic attack. (22nd March 2018) - Pedersen, Kenneth Bruun; Madsen, Charlotte; Sandgaard, Niels C.F.; Diederichsen, Axel C.P.; Bak, Søren; Brandes, Axel
Abstract: Background: Atrial fibrillation (AF) is a major risk factor of stroke, but the association between AF and transient ischemic attack (TIA) is less clear. Despite this, patients with TIA are included in stroke trials. Aims: To determine the 1‐year incidence of AF in TIA patients using an insertable cardiac monitor (ICM); second, to determine factors associated with incident AF in these patients. Methods: Prospective cohort study of patients with TIA with normal standard electrocardiogram (ECG) and 72‐hour Holter monitoring (HM). Exclusion criteria were as follows: age < 18 or > 81 years; prior AF/stroke; ongoing oral anticoagulation therapy or contraindication for it; significant carotid artery stenosis; uncertain TIA diagnosis. Eligible patients received an ICM and were followed for 12 months. Results: From November 2013 to October 2015, 809 patients were diagnosed with TIA. In total, 235 patients were eligible. Nine (3.8%) of these had AF on standard ECG or HM. Of the remaining patients, 121 refused ICM implantation. In total, 105 patients (median age 65.4 years [range 27.1–80.8], 46% males) received an ICM, which revealed AF in 7 (6.7%). Factors associated with new‐onset AF were a history of recurrent TIA (odds ratio [OR] 11.5, 95% confidence interval [CI] 2.1–63.6) and heart failure (OR 12.7, 95% CI 1.71–96.83). Conclusions: The 1‐year incidence of AF in TIA patients with normal ECG and HM was 6.7% using an ICM. Factors associated with development of AF were recurrent TIA and heart failure.